A Rhodopsin-Like Gene May Be Associated With the Light-Sensitivity of Adult Pacific Oyster Crassostrea gigas - Wu, Changlu; Jiang, Qiuyun; Wei, Lei; Cai, Zhongqiang; Chen, Jun; Yu, Wenchao; He, Cheng; Wang, Jiao; Guo, Wen; Wang, Xiaotong (Frontiers in Physiology, 2018)
Light-sensitivity is important for mollusc survival, as it plays a vital role in reproduction and predator avoidance. Light-sensitivity has been demonstrated in the adult Pacific oyster Crassostrea gigas, but the genes associated with light perception remain unclear. In the present study, we designed experiments to identify the genes associated with light-sensitivity in adult oysters. First, we assessed the Pacific oyster genome and identified 368 genes annotated with the terms associated with light-sensitivity. Second, the function of the above four rhodopsin-like superfamily member genes was tested by using RNAi. The results showed that the highest level of mRNA expression of the vision-related genes was in the mantle; however, this finding is not true for all oyster genes. Interestingly, we also found four rhodopsin-like superfamily member genes expressed at an exceptionally high level in the mantle tissue. In the RNAi experiment, when one of rhodopsin-like superfamily member genes (CGI_1001253) was inhibited, the light-sensitivity capacity of the injected oysters was significantly reduced, suggesting that CGI_10012534 may be associated with light-sensitivity in the adult Pacific oyster.